Penegakan Hukum terhadap Budaya Omed-omedan di Banjar Kaja Desa Sesetan - Tri Bagus Manik Naradhipam; I Wayan Wesna Astara; I Made Minggu Widyantara (Warmadewa Press, 2025)
Law enforcement against omed-omedan culture needs to be reviewed further because this is related to indigenous peoples and religious rituals, omed-omedan culture is a culture carried out by the banjar kaja community of sesetan village in carrying out this culture there is friction between the implementers of the tradition, namely friction such as hugging and kissing. The formulation of the problem in this thesis How is the omed omedan tradition reviewed from the pornography law? and how is law enforcement based on the pornography law against the omed omedan tradition?. The purpose of this research is to analyze the omed-omedan culture in terms of the pornography law and analyze law enforcement based on the pornography law against omed-omedan culture. The method used is experimental with a sociology approach. The data sources used are primary data and secondary data from legal documents. The results of this study explain how omed-omedan is viewed from the pornography law and law enforcement based on the law against the omed-omedan tradition.